Pengaruh Media Audio Visual terhadap Hasil Belajar Matematika - Fargil Prasetia (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The Effect of Media Audio Visual on Mathematics Achievement. This experimental research aimed to determine the effect on mathematics achievement. The benefit of using audio-visual media is to facilitate learners in understanding mathematics. The design of the research is true experimental design with posttest only control design. The research was conducted at the sixth grade students at SD Negeri Duren Tiga 01 Pagi, South Jakarta. The research sample was determined by simple random sampling technique, were taken each 20 students for the experimental group and the control group. After two sample groups were given different treatment, each sample group were given a posttest with the instrument consists of 30 items on the subject Flat with four alternative answers to multiple choice questions. The instrument has been tested in advance and validated content (content validity) and construct (construct validity). Analysis of the data used test, with the first test of normality and homogeneity. The results showed that there is significant effect of media audio visual on mathematics achievement.